2022
DOI: 10.1007/s12672-022-00494-1
|View full text |Cite
|
Sign up to set email alerts
|

KLF14 targets ITGB1 to inhibit the progression of cervical cancer via the PI3K/AKT signalling pathway

Abstract: Our study aimed to determine whether Krüppel-like factor 14 (KLF14) inhibits the proliferation and promotes the apoptosis of cervical cancer cells through integrin β1 (ITGB1). Immunohistochemistry was performed to determine the expression of KLF14. The effect of KLF14 on the proliferation of cervical cancer cells was verified by Cell Counting Kit-8 (CCK-8) assays, colony formation assays and in vivo experiments. The effect of KLF14 on cervical cancer cell apoptosis was detected by flow cytometry. The targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…In previous studies, Itgb1 was highly expressed in glioma, osteosarcoma, and bone marrow mesenchymal stem cells.Itgb1 is a member of the ITG family [21,22], which is closely associated with apoptosis. Itgb1 enhances the radiation resistance of non-small cell lung cancer cells by regulating the DNA damage response [23]and YAP1-induced epithelial-mesenchymal transition [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Itgb1 was highly expressed in glioma, osteosarcoma, and bone marrow mesenchymal stem cells.Itgb1 is a member of the ITG family [21,22], which is closely associated with apoptosis. Itgb1 enhances the radiation resistance of non-small cell lung cancer cells by regulating the DNA damage response [23]and YAP1-induced epithelial-mesenchymal transition [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as a member of the integrin family, ITGB1 connects the extracellular matrix (ECM) to the intracellular tyrosine kinase PI3K, leading to the activation of PI3K/Akt signaling [ 140 ]. Then, ITGB1-induced over-activation of PI3K/Akt signaling causes an uncontrolled cell proliferation [ 141 ]. Further investigations conducted by the same team revealed that ITGB1 expression was regulated by miR-361-3p in CC cells, in a reverse manner, indicating that miR-361-3p could bind to the ITGB1 to suppress its function for further reduction of cell proliferation and invasion.…”
Section: How Circular Rnas Control Cervical Cancer Progression? a Foc...mentioning
confidence: 99%
“…KLF14 activates this signaling by enhancing the activation of AKT kinase and preventing AKT phosphorylation ( 38 ). Nevertheless, KLF14 simultaneously suppresses cervical cancer progression by inhibiting integrin beta 1 transcription, which upregulates key molecules in the PI3K/AKT signaling, including AKT and p-AKT, representing an indirect inhibitory effect of KLF14 on PI3K/AKT ( 39 ). The interaction between KLF14 and PI3K is also bidirectional.…”
Section: Klfs-mediated Molecular Regulationmentioning
confidence: 99%